Effectiveness of Single-Tablet Combination Therapy in Improving Adherence and Persistence and the Relation to Clinical and Economic Outcomes - Carly J. Paoli; Jörg Linder; Khushboo Gurjar; Deepika Thakur; Julie Wyckmans; Stacy Grieve (Journal of Health Economics and Outcomes Research)
# Background Single-tablet combination therapies (STCTs) combine multiple drugs into one formulation, making drug administration more convenient for patients. STCTs were developed to address concerns with treatment adherence and persistence, but the impact of STCT use is not fully understood across indications.